2018
DOI: 10.1242/jeb.182113
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical effects of augmented ankle power output during human walking

Abstract: The plantarflexor muscles are critical for forward propulsion and leg swing initiation during the push-off phase of walking, serving to modulate step length and walking speed. However, reduced ankle power output is common in aging and gait pathology, and is considered a root biomechanical cause of compensatory increases in hip power generation and increased metabolic energy cost. There is a critical need for mechanistic insight into the precise influence of ankle power output on patterns of mechanical power ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…1). We calculated prosthetic-limb stance time as the amount of time we detected a vertical ground reaction force greater than 10% of the subject’s body weight, averaged it over the previous five strides [25] to reduce subjects’ tendency to generate large stride-to-stride corrections, and updated it after each ipsilateral toe-off event (Fig. 1, blue dot).…”
Section: Methodsmentioning
confidence: 99%
“…1). We calculated prosthetic-limb stance time as the amount of time we detected a vertical ground reaction force greater than 10% of the subject’s body weight, averaged it over the previous five strides [25] to reduce subjects’ tendency to generate large stride-to-stride corrections, and updated it after each ipsilateral toe-off event (Fig. 1, blue dot).…”
Section: Methodsmentioning
confidence: 99%
“…Growing indirect evidence suggests that a distal-to-proximal redistribution of muscular workload during walking may come with a significant metabolic penalty rooted in inter-muscular differences in muscle-tendon architecture. Specifically, with their short muscle fibers and long, compliant series elastic tendons, we (Fickey et al 2018; Browne & Franz 2019) and others (Sawicki et al 2009;Huang et al 2015) have suggested that muscle-tendon units spanning the ankle are far more economical for force generation in walking than those spanning the hip, which have much longer muscle fibers and relatively shorter and less compliant tendons. However, despite its potential relevance to walking economy in aging and gait pathology, this theory has not yet been supported by direct experimental manipulation or measurement.…”
Section: Introductionmentioning
confidence: 72%
“…While the effects in our study in healthy subjects do not directly translate to a patient population, the magnitude of our effects after just one training session are encouraging for future research in a patient population, especially considering that healthy subjects are subject to ceiling effects as their baseline is assumed to be roughly optimal. Moreover, previous studies have shown that training increases in muscle strength alone do not translate to functional increases in ankle moment during walking, and call for rehabilitation methods that target propulsive deficits in the context of walking [1]. Our paradigm has the potential to improve locomotor patterns through training favorable biomechanical changes in both posture and ankle plantar-flexors during walking, with potential to provide greater translation to habitual speed walking in the community setting than muscle strengthening alone, or other gait therapies that utilize fixed speed treadmills [1], [3], [18], [24].…”
Section: Discussionmentioning
confidence: 99%
“…Ambulation is critical to performing activities of daily living, including self-care and community engagement. Walking ability, commonly assessed by walking speed, decreases with age and is affected by numerous neurological conditions [1], [2]. As our aging population increases, there is a critical need for rehabilitation techniques that are effective in retraining walking ability to prolong independent living and quality of life for these individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation